+0  
 
+1
170
1
avatar+1117 

(5xy^2 + 1) (xy^2 - 4) 

 May 21, 2019
 #1
avatar+106535 
+3

F  =  multiply the first term in each set of parentheses together

This gives us  5xy^2 * xy^2  =  5x^2y^4

 

O =   multiply  the " outside terms" together

This gives us  5xy^2 * (-4)  =  -20xy^2

 

I = multiply the "inside  terms" together

This gives us   1 * xy^2  =  xy^2

 

L  =  multiply the last term in each set of parentheses together

This gives us  (+1) (-4)  =  - 4

 

So....combining the terms we get

 

5x^2y^4 - 20xy^2 + xy^2 - 4  =

 

5x^2y^4 - 19xy^2 - 4

 

 

cool cool cool

 May 21, 2019

27 Online Users